Anomalous Papillary Muscle Insertion Causing Dynamic Left Ventricular Outflow Tract Obstruction without Hypertrophic Obstructive Cardiomyopathy - Ravi Korabathina; Katherine Chiu; Hugh M. van Gelder; Arthur Labovitz (Case Reports in Cardiology)
Anomalous papillary muscle insertion directly into the surface of the mitral valve leaflet is rare, especially in a subject without apparent evidence of hypertrophic cardiomyopathy. We present a case of this isolated congenital malformation producing two hemodynamic sequelae of dynamic left ventricular outflow tract obstruction and severe mitral regurgitation.